Revd. W. Cockran's journal, Aug. '39 to Aug. '40 - Cockran, William (Adam Matthew Digital, 1839)
Journal entries describing William Cockran's missionary life and work amongst Native Americans, relating his opinions of their culture and the impact of Christianity